Pembuatan Indeks Ensiklopedi Koleksi Dinas Perpustakaan dan Kearsipan Kota Padang Panjang - Dewi, Rosmita; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This paper aims to discuss about how to create an index of encyclopedic collection in the Library and Archive Department of Padang Panjang City. It aims to describe the making of encyclopedic collection index in the Library and Archive Department of Padang Panjang City in order to make it easier to find information needed at any time. Data analysis used descriptive method. The data were collected through observation or direct research and documentation at the reference service at the Library and Archive Department of Padang Panjang City. From data analysis through observation and direct research, could be collected as many as 164 copies.Based on analyzing the data, it can be concluded that the steps in making the encyclopedic collection index are as follows: There are several important steps in making of encyclopedic index such as: (a) initial observation of documents, is observing and ensuring documents to be indexed are in reference services ; (b) selecting collections to be indexed by collecting all encyclopedic collections incorporated with other reference collections; (c) records the collection descriptions with determining the headline of the main entry, the collection title, the collection number, the rising city, the publisher and the year of publication; (d) keyword determination can be obtained from the collection title or read the discussion of the collection information; (e) arrange indexes based on author index, keyword index, and title index; (f) typing indexes using a computer.Keyword : encyclopedia, index.